PENGARUH MEDIA DASAR DAN BENZILADENIN (BA) TERHADAP PEMBESARAN SEEDLING ANGGREK Dendrobium IN VITRO - Adryade Reshi Gusta; Dwi Hapsoro; Nyimas Sa’diyah; Yusnita Yusnita (JURNAL AGROTROPIKA, 2011)
Orchid such as Dendrobium is more commonly propagated in vitro by using tis-sue culture techniques. In tissue culture, the type and composition of media and plant growth regulator was very crucial. The research was aimed to study the effect of media and plant growth regulator on growth of Dendrobium seedlings in vitro and was conducted in Plant Tissue Culture Laboratory, Faculty of Agriculture, University of Lampung, from April 2010 until October 2010. The experiment was carried out in a completely randomized design with three replicates. Treatments were arranged as 2 x 3 factorial design with media (½ MS and modified ½ MS with high P and low N) as the first factor and three concentrations of benzyl-adenine (0, 5, and 10 mg/l) as the second factor. Each experimental unit consisted of 3 culture bottles each of which containing 2 five-month-old seedlings. The result showed that both media was not significantly affected the growth of Dendrobium seedlings. Whereas, the addition of benzyl-adenine (BA) at 5 mg/l and 10 mg/l in both of media was able to increase shoot number from 2.8 to 5.2-5.4 and increase leave number from 9.2 to 18.0-18.2. Overall, the application of benzyl-adenine decreased shoot height (from 3.7 to 3.0-2.7 cm), root number (from 2.7 to 1.3-0.8), and root length (from 1.6 to 1.0-0.8 cm). Keyword : Dendrobium in vitro, seedlings growth.